Study on the Competitiveness of the Romanian Meat Processing Industry - Silvius Stanciu; Raluca Daniela Rizea; Anca Gabriela Ilie (Amfiteatru Economic Journal, 2015)
Meat processing represents a strategic sector that can significantly contribute to local food industry competitiveness and national food security. The generous natural resources available to Romania and the tradition in animal husbandry can provide adequate raw materials for the processing industry in order to cover domestic consumption needs and obtain substantial revenues by export. Currently, Romanian meat market is dependent on the imports of meat, as carcasses or processed products. There have been mainly live animals or semi-finished products which are exported, fact which led to an imbalance of trade and to low revenues for the domestic meat industry. This article proposes an analysis of the local meat processing industry in terms of production, consumption and trade transactions, assessed in the international context of the meat market. The study indicates that in the last few years, Romania has recorded significant progress in the meat processing and production domain; nevertheless, the financial performance of the local companies is inferior to that of the EU companies. Except the poultry meat and mutton sectors, in which the export value exceeds imports, the other sectors show a deficit, the domestic demand not being covered. The low concentration degree of the companies from the meat processing industry show a continued market fragmentation and a growth potential for the existing companies.
Keywords: L11; L25; L66; 330; competitiveness; processing; meat; meat industry; consumption